Genetic and Biochemical Evidence That Enterococcus faecalis Gr17 Produces a Novel and Sec-Dependent Bacteriocin, Enterocin Gr17 - Liu, Guorong; Wang, Yao; Li, Xue; Hao, Xu; Xu, Duoxia; Zhou, Yingning; Mehmood, Arshad; Wang, Chengtao (Frontiers in Microbiology, 2019)
Bacteriocins are ribosomally synthesized antibacterial peptides or proteins from microorganisms. We report a novel bacteriocin producing strain, Enterococcus faecalis Gr17, that was isolated from the Chinese traditional low-salt fermented whole fish product Suan yu. E. faecalis Gr17 displayed potent antibacterial activity against foodborne pathogenic and spoilage bacteria. The complete genome of E. faecalis Gr17 contained one circular chromosome and plasmid. The gene cluster of a novel bacteriocin designated enterocin Gr17 was identified. The enterocin Gr17 structural gene encodes a precursor of the bacteriocin. Two other transporter genes and an immunity gene within two divergent operons were identified as being associated with enterocin Gr17 secretion and protection. The novel enterocin Gr17 was purified by ammonium sulfate precipitation, cation exchange, gel filtration, and reverse-phase high-performance liquid chromatography. The molecular weight of enterocin Gr17 was 4531.01 Da as determined by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and its mature amino acid sequence of enterocin Gr17 was RSYGNGVYCNNSKCWVNWGEAKENIIGIVISGWATGLAGMGR. Sequence alignment revealed that enterocin Gr17 is a class IIa bacteriocin with similarities to enterocin P. The merits of bactericidal activity, sensitivity to enzymes, and pronounced stability to chemicals, temperature (60 ℃, 30 min and 121 ℃, 15 min), and pH (2-10) indicated practicality and safety of enterocin Gr17 in the food industry. The complete genome information of E. faecalis Gr17 will improve the understanding of the biosynthetic mechanism of enterocin Gr17, which has potential value as a food biopreservative.